US–Euro Area Monetary Policy Interdependence – New Evidence from Taylor Rule Based VECMs - Ansgar Belke; Yuhua Cui (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper analyses the monetary policy interdependence between the European Central Bank (ECB) and the Federal Reserve (Fed) for the period 1999-2006. Two models are specified: a partial Vector Error Correction Model (VECM) and a general VECM. In the partial VECM, we look for a long-run interdependent relationship between the interest rates of the two currency areas and specify the Taylor Rule terms as exogenous variables. In the general VECM, we regard all variables as endogenous, and look for long-run equilibrium relationships among them, which may reveal monetary policy interdependence between the two central banks. Weak exogeneity is checked in both models in order to establish a possible leader-follower relationship. The empirical results of both models indicate interdependence between the ECB and the Fed, but only the general VECM testifies a leader-follower pattern between the two central banks. According to this pattern, the ECB does follow the Fed.
Keywords: E43; E58; 330; Monetary policy; interdependence; European Central Bank; Federal Reserve; Taylor rule; VECM; Geldpolitik; Taylor-Regel; Zinsparität; Fehlerkorrekturmodell; Schätzung; Deutschland; USA